Mathematics for business, economics and finance - Shannon, John. (Brisbane : John Wiley and Sons, 1995)
This book is about: A review of basic algebra; Graphical lenear models; Solving systems of linear simultaneous equations; Matrix algebra; Matrix applications; ...
Keywords: Business mathematics; Business mathematics -- Problems, exercises, etc; Business mathematics